Halfway houses: liminality and the haunted house motif in popular American Gothic fiction - Janicker, Rebecca (2014)
Halfway Houses examines popular American Gothic fiction through a critical focus on what I call the ‘haunted house motif’. This motif, I argue, creates a distinctive narrative space, characterised by the key quality of liminality, in which historical events and processes impact upon the present. Haunted house stories provide imaginative opportunities to keep the past alive while highlighting the complexities of the culture in which they are written. My chosen authors, H. P. Lovecraft, Richard Matheson and Stephen King, use the haunted house motif to engage with political and ideological perspectives important to an understanding of American history and culture. Analysing their fiction, I argue that in “The Dreams in the Witch House” (1933) Lovecraft uses haunting to address concerns about industrialisation, urbanisation and modernisation in the early part of the twentieth century, endorsing both progressive and conservative ideologies. Similarly, Matheson’s haunting highlights issues of 1950s suburbanisation in A Stir of Echoes (1958) and changing social mores about the American family during the 1970s and 1980s in Earthbound (1982; 1989), critiquing conformist culture whilst stopping short of overturning it. Lastly, as a product of the counterculture, King explores new kinds of haunted spaces relevant to the American experience from the 1970s onwards. In The Shining (1977) he draws on haunting to problematise inequalities of masculinity, class and capitalism, and in Christine (1983), at a time of re- emerging conservative politics, he critiques Reaganite nostalgia for the supposed ‘golden age’ of the 1950s. At the close of the twentieth century, haunting in Bag of Bones (1998) reappraises American guilt about race and the legacy of slavery. Overall, my thesis shows that the haunted house motif adapts to the ever-changing conditions of American modernity and that the liminality of haunting addresses the concomitant social unease that such changes bring.